Diurnal variability of inner-shelf circulation in the lee of a cape under upwelling conditions - Lamas, Luísa (2019)
The nearshore circulation in the lee of a cape under upwelling conditions was studied using in-situ data from 3 consecutive summers (2006–2008). Focus was given to a period between 20 July and 04 August 2006 to study the diurnal variability of the cross-shelf circulation. This period was chosen because it had a steady upwelling-favourable wind condition modulated by a diurnal cycle much similar to sea breeze. The daily variability of the observed cross-shelf circulation consisted of three distinct periods: a morning period with a 3-layer vertical structure with onshore velocities at mid-depth, a mid-day period where the flow is reversed and has a 2-layer structure with onshore velocities at the surface and offshore flow below, and, lastly, in the evening, a 2-layer period with intensified offshore velocities at the surface and onshore flow at the bottom. The observed cross-shelf circulation showed a peculiar vertical shape and diurnal variability different from several other systems described in literature. We hypothesize that the flow reversal of the cross-shelf circulation results as a response to the rapid change of the wind magnitude and direction at mid-day with the presence of the cape north of the mooring site influencing this response. A numerical modelling experiment exclusively forced by winds simulated successfully most of the circulation at the ADCP site, especially the mid-day reversal and the evening's upwelling-type structure. This supports the hypothesis that the cross-shelf circulation at diurnal timescales is mostly wind-driven. By analysing the 3D circulation in the vicinity of Cape Sines we came to the conclusion that the diurnal variability of the wind and the flow interaction with topography are responsible for the circulation variability at the ADCP site, though only a small region in the south of the cape showed a similar diurnal variability. The fact that the wind diurnally undergoes relaxation and intensification strongly affects the circulation, promoting superficial onshore flows in the leeside of Cape Sines. Despite the small-scale nature of the observed cross-shelf circulation, onshore flows as the ones described in this study can be particularly helpful to understand the transport and settlement of larvae in this region and in other regions with similar topography and wind characteristics.